Rethink the education system - Abd Razak, Dzulkifli (2010)
THE recent report on the crashing of the roof of the library at the 184yearold Malacca High School is an eyeopener — not in a direct sense but in an oblique way, especially in light of the national debates on whether the Ujian Penilaian Sekolah Rendah (UPSR) and Penilaian Menengah Rendah (PMR) examinations should be abolished. Although the outcomes of the roundtable talks have already been made known, the debate is by no means over. This is where you can draw an analogy between the “crashing roof” event and the debate.